Partisipasi Siswa dan Guru SMAN 13 Bandung Dalam Peningkatan Pemahaman Hak Kekayaan Intelektual - Amirulloh, Muhamad; Novianty , Helitha (Jurnal Kajian Budaya dan Humaniora, 2023)
Teachers and students of SMAN 13 Bandung have a poor level of understanding of Intellectual Property Rights (IPR) because they have only received the IPR socialization once. PPM Unpad activities aim to improve the understanding of IPR of students and teachers to be motivated in creating intellectual work. With a participatory method, IPR briefing for teachers and students of SMAN 13 was carried out in the subject of Entrepreneurship Education, for 4 weeks. As a result, there was an increase in teacher and student understanding of IPR by an average of 17%, from the pre-test quiz score of 42% to 59% in the post-test quiz.